The analysis of 6- and 24-hour iodine-131 thyroid uptake in patients with Graves' disease at Universitas Hospital - Horn, Je'nine ([Bloemfontein?] : Central University of Technology, Free State, 2007)
In the South African Health Services (SAHS) it is each health worker’s responsibility to find ways to reduce health care cost and improve health service to the public. The measurement of radioactive iodine uptake (RAIU) by the thyroid gland for diagnostic purposes has been used as early as the 1940s. The 24-hour (hr) iodine-131 (131I) uptake measurement is traditionally used for the calculation of the 131I administered activity for therapy dosage. This entails that the patient’s hospitalisation is prolonged, which increases the costs. The literature also indicates that the 24-hr 131I uptake value can be discarded and only the 6-hr 131I uptake measurement is needed to calculate administered activity for therapeutic dosages for Graves’ patients. Therefore, if it can be confirmed that the 6-hr 131I uptake measurement alone is needed, the SAHS could decrease hospitalisation costs. The overall goal of the investigation was to analyse the 6-hr and 24-hr 131I uptake measurements of patients with Graves’ disease at the Universitas Hospital. The aim was to determine the relationship between the 6-hr and 24- hr RAIU values to establish the therapeutic dosage for Graves’ disease. To achieve the aim, three objectives were set. First, to serve as a background to the investigation, a literature survey relating to the RAIU measurements of patients with Graves’ disease was made. Second, a retrospective analysis was performed by collecting the 6-hr and 24-hr 131I uptake measurements of patients with proven Graves’ disease at the Universitas Nuclear Medicine Department (UNMD). Finally, the data obtained from the retrospective analysis was analysed, summarised and compared to answer the investigation questions. The investigation group included patients with confirmed Graves’ disease who had undergone both the 6- and 24-hr 131I RAIU at the Universitas Hospital from the beginning of 2004 to the end of 2005. Graves’ disease is confirmed by the following factors at the UNMD, namely: Suppressed TSH, elevated T4 and T3 values, an increased uptake on the 99mTc-pertechnetate scan and increased 6- and 24-hr 131I RAIU values. The UNMD statistics show that 178 patients were diagnosed with Graves’ disease during this period. The patients of the investigation group included both male and female patients from different races, ranging from 15-75 years. In order to increase the validity of the investigation, all factors that could influence the accuracy of the 131I thyroid uptake test were excluded. After the exclusion and inclusion criteria had been applied, the final investigation group was made up of 124 Graves’ disease patients. The data obtained from the patient files was noted on the different data sheets (see Appendix A) for further analysis. The information from these data sheets was then used to obtain the investigation results. The Department of Biostatistics of the University of the Free State (UFS) was consulted for recommendations regarding the management of data and the processing of results. All values were summarised by means and Standard Deviations (SD) or percentiles. Mean or median differences were calculated with a 95% Confidence Interval (CI). A regression analysis was made between the 6-hr and 24-hr 131I RAIU values. The highest RAIU value is the best to calculate the therapeutic dosage, as this gives a true reflection of the thyroid function of a Graves’ disease patient. In the investigation group the median of the 24-hr 131I RAIU values was higher than the 6-hr 131I RAIU values. The findings showed that the 24-hr 131I RAIU in most of the investigation group was the highest value and most effective to calculate the 131I therapeutic dosage. At a time when research-based practice is taking on an increasingly important role, it is essential for nuclear medicine departments to make evidence-based recommendations. This investigation found that the correlation between the 6-hr and 24-hr RAIU clearly justified the cost spent on Graves’ disease patients who must stay overnight for the 24-hr 131I RAIU procedure.
Thesis (M.Tech.)(Nuclear Medicine) -- Central University of Technology, free State, 2007
Keywords: Central University of Technology, Free State - Dissertations; Dissertations, academic - South Africa - Bloemfontein; Graves' disease - drug therapy; Iodine - therapeutic use; Iodine compounds - therapeutic use; Drug monitoring; Iodine radioisotopes; Thyroid gland diseases; Thyroid gland diseases - drug therapy